2010
DOI: 10.4028/www.scientific.net/amm.29-32.1436
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Heat-Transfer Simulation Based on CFD and Experimental Study during High-Pressure Gas Quenching

Abstract: High-pressure gas quenching is the heat treatment technology which quenches the works by use of high-pressure and high-speed flow gas. FLUENT software is used to simulate the process of gas-solid coupling flow and heat transfer in the nozzle-type vacuum high-pressure gas quenching furnace. The hot wire anemometer is used to measure the inlet velocities of nozzles, which provides the boundary conditions for computer simulation. By the computer simulation, the gas flow fields, work temperature fields and work co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The effect of vortical structures and loading pattern on the heat treatment process and temperature history of small scale products had been mentioned in the numerical study of Wang and Shang [31] who investigated the flow and heat exchange in the high-pressure gas quenching chamber.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of vortical structures and loading pattern on the heat treatment process and temperature history of small scale products had been mentioned in the numerical study of Wang and Shang [31] who investigated the flow and heat exchange in the high-pressure gas quenching chamber.…”
Section: Introductionmentioning
confidence: 99%
“…Arkhazloo et al [9], investigating the thermal interactions inside an industrial gas-fired furnace, reported the significant effect of stacking patterns (such as their relative locations and distances) on the uniformity of the tempering process. Such influence on the temperature uniformity of the product was also mentioned by Wang and Shang [15] and Macchion et al [32] in their numerical studies of small-scale steel parts' heat treatment within a high pressure gas quenching chamber. According to Macchion et al [32], the temperature uniformity of the product was significantly affected by the position of parts within the furnace.…”
Section: Introductionmentioning
confidence: 56%
“…Recently, computational fluid dynamics (CFD), offering the simultaneous analysis of turbulent fluid flow and conjugate heat transfer, has been employed in several studies on the thermal analysis of industrial furnaces [13][14][15][16]. Studies comprising Harish et al [17] and Zhang et al [13], or recently published papers such as those by Mayr et al [18], Tang et al [19], and Liu et al [20], employed CFD simulations to investigate the heating procedure in different continuous reheating furnaces (for instance, pusher type furnaces or walking beam furnaces).…”
Section: Introductionmentioning
confidence: 99%